Population Survey Data Informing the Therapeutic Potential of Classic and Novel Phenethylamine, Tryptamine, and Lysergamide Psychedelics - Sexton, James D.; Nichols, Charles D.; Hendricks, Peter S. (Frontiers in Psychiatry, 2020)
Introduction: The majority of contemporary psychedelic research has focused on ayahuasca, LSD, and psilocybin, though there are hundreds of novel psychedelic compounds that may have clinical utility. The purpose of the present study was to evaluate the therapeutic potential of classic and novel phenethylamine, tryptamine, and lysergamide psychedelics via a large, nationally representative population-based survey. Methods: We tested the unique associations of lifetime classic and novel phenethylamine, tryptamine, and lysergamide psychedelics with past month psychological distress and past year suicidality among respondents pooled from years 2008-2017 of the National Survey on Drug Use and Health (weighted N = 260,964,827). Results: Lifetime classic tryptamine use was associated with a decreased odds of past month psychological distress (aOR = 0.76; [0.69 – 0.83]) and past year suicidal thinking (aOR = 0.79; [0.72 – 0.87]). Lifetime novel phenethylamine use, on the other hand, was associated with an increased odds of past year suicidal thinking (aOR = 1.44; [1.06 – 1.95]) and past year suicidal planning (aOR = 1.60; [1.06 – 2.41]). No other significant associations were found. Discussion and Conclusions: These findings, which may be driven by differences in pharmacodynamics, suggest that classic tryptamines may hold the greatest therapeutic potential of the psychedelics, whereas novel phenethylamines may pose risk for harm. The present findings thus support continued research on the clinical application of classic tryptamines. Though the current results caution against the clinical utility of novel phenethylamines, further study of these and other novel psychedelic substances is nonetheless warranted to better understand their potential application.